2021
DOI: 10.1097/mco.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms of illness and emotional distress in advanced cancer cachexia

Abstract: Purpose of reviewCachexia induces both physical and psychological symptoms of illness in patients with advanced cancer and may generate emotional distress in patients and families. However, physical symptoms of cachexia received the most emphasis. The aims of this review are to elucidate a link between systemic inflammation underlying cachexia and psychological symptoms and emotional distress, and to advance care strategy for management of psychological symptoms and emotional distress in patients and families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Accumulating evidence has shown that systemic inflammation is involved in the mechanisms responsible for cancer cachexia and that proinflammatory cytokines generate various cachexia-related physical and psychological symptoms through alternations in the central nervous system in patients with advanced cancer. 3 , 4 In addition, these symptoms are worsened by cancer treatments and are associated with the emotional distress experienced by patients and families. 4–6 Therefore, the latest evidence-based clinical practice guidelines on the management of cancer cachexia, clinical nutrition in cancer, and end-of-life care for cancer patients have advocated holistic multimodal interventions, which is an approach addressing not only physical health but also psychological, emotional, and social well-being issues by all health care professionals (HCPs) including psychologists and social workers, to meet the physiological and psychological needs of patients and families despite the lack of a clear mandate for diagnosis and treatment of the cachexia-related problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that systemic inflammation is involved in the mechanisms responsible for cancer cachexia and that proinflammatory cytokines generate various cachexia-related physical and psychological symptoms through alternations in the central nervous system in patients with advanced cancer. 3 , 4 In addition, these symptoms are worsened by cancer treatments and are associated with the emotional distress experienced by patients and families. 4–6 Therefore, the latest evidence-based clinical practice guidelines on the management of cancer cachexia, clinical nutrition in cancer, and end-of-life care for cancer patients have advocated holistic multimodal interventions, which is an approach addressing not only physical health but also psychological, emotional, and social well-being issues by all health care professionals (HCPs) including psychologists and social workers, to meet the physiological and psychological needs of patients and families despite the lack of a clear mandate for diagnosis and treatment of the cachexia-related problems.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 In addition, these symptoms are worsened by cancer treatments and are associated with the emotional distress experienced by patients and families. 4–6 Therefore, the latest evidence-based clinical practice guidelines on the management of cancer cachexia, clinical nutrition in cancer, and end-of-life care for cancer patients have advocated holistic multimodal interventions, which is an approach addressing not only physical health but also psychological, emotional, and social well-being issues by all health care professionals (HCPs) including psychologists and social workers, to meet the physiological and psychological needs of patients and families despite the lack of a clear mandate for diagnosis and treatment of the cachexia-related problems. 7–10 Although such multimodal approach attends to restoring or sustaining the physical body, it also alleviates distress and supports connectedness with others.…”
Section: Introductionmentioning
confidence: 99%
“…It can help identify individuals' psychological characteristics such as intelligence, personality, and psychological health differences to determine their relative strengths and weaknesses. This will provide a quantitative basis for teaching students according to their aptitude and using their talents best [ 9 ]. In analyzing herdsman's credit behavior, the individual differences between herdsmen's credit behavior are obtained by analyzing and identifying their emotional and psychological states.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care may improve psychological conditions by providing patients with the skills to cope effectively with lifethreatening illness (33). We speculate that it is plausible that inpatient palliative care is more effective for enhancing patients' adaptive coping strategies (34). Future work should examine whether patients' coping skills mediate the effect of different integration models of palliative care intervention on psychological distress in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%